2008
DOI: 10.2134/jeq2006.0547
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cover Crop and Reduced Cultivation for Reducing Nitrate Leaching in Ireland

Abstract: Nitrate (NO(3)) loss from arable systems to surface and groundwater has attracted considerable attention in recent years in Ireland. Little information exists under Irish conditions, which are wet and temperate, on the effects of winter cover crops and different tillage techniques on NO(3) leaching. This study investigated the efficacy of such practices in reducing NO(3) leaching from a spring barley (Hordeum vulgare L.) system in the Barrow River valley, southeast Ireland. The study compared the effect of two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
28
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(38 citation statements)
references
References 18 publications
(25 reference statements)
7
28
0
3
Order By: Relevance
“…This study adds to the evidence of Hooker et al (2008) and Premrov et al (2014) who found no significant difference in leaching from CT and MT soils in Ireland.…”
Section: Leaching Losses Post-ploughing and Fertilisationsupporting
confidence: 60%
See 1 more Smart Citation
“…This study adds to the evidence of Hooker et al (2008) and Premrov et al (2014) who found no significant difference in leaching from CT and MT soils in Ireland.…”
Section: Leaching Losses Post-ploughing and Fertilisationsupporting
confidence: 60%
“…There are conflicting reports on the effect of tillage method on N leaching. Some authors reported a reduction in N leaching losses in arable crops (Dinnes et al, 2002;Syswerda et al, 2012) while others did not see this effect in tillage soils in Ireland (Hooker et al, 2008;Premrov et al, 1014). However this might not be true for permanent grassland and the effect of tillage method may also depend on soil type (Hansen et al, 1997) as well as climatic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Catch crops decreased mineral nitrogen (N min ) content in both soil layers (0-40 cm and 40-80 cm) compared with the treatment without catch crops. Our research data agree with those of other researchers, who found less nitrogen (not exceeding European Union's allowable limits) in soil leachate after cultivation of catch crops in a crop rotation (Hooker et al, 2008). Legumes, as the postharvest catch crop, are not effective for nitrogen capture from the soil due to symbiotic nitrogen fixation.…”
Section: Discussionsupporting
confidence: 91%
“…Nitrate leaching for spring wheat (Table 3) was within the range reported in other studies for spring wheat (4 to 12 g N m´2; [21]) or spring cereals, e.g., 0.7 to 7.5 g N m´2 [32] and 1.61 to 9.63 g N m´2 [33]. The percentage of the NO 3 -N leaching to the fertilizer N input (14%) was in range of the 0.10 reported by Uhlen [21] for spring wheat grown in a similar climate.…”
Section: Discussionsupporting
confidence: 85%